The Signaling Pathways, and Therapeutic Targets of Antiviral Agents: Focusing on the Antiviral Approaches and Clinical Perspectives of Anthocyanins in the Management of Viral Diseases - Mohammadi Pour, Pardis; Fakhri, Sajad; Asgary, Sedigheh; Farzaei, Mohammad Hosein; Echeverría, Javier (Frontiers in Pharmacology, 2019)
As the leading causes of death worldwide, viruses significantly affect global health. Despite the rapid progress in human healthcare, yet there are few virucidal and antiviral therapies to be efficient enough. The rapid emergence of resistance, and high costs, as well as the related side effects of synthetic antiviral drugs, raise the needs to identify novel, effective, and safe alternatives against viral diseases. Nature has been of the most exceptional help and source of inspiration for developing novel multi-target antiviral compounds affecting several steps of the viral life cycle and host proteins. For that matter and due to safety and efficacy limitations as well as high resistance rate of conventional therapies, hundreds of natural molecules are preferred over the synthetic drugs. Besides, natural antiviral agents have shown acceptable antiviral value in both preclinical and clinical trials. This is the first review regarding molecular and cellular pathways of the virus life cycle, treatment strategies, and therapeutic targets of several viral diseases were reviewed with a particular focus on anthocyanins as promising natural compounds for significant antiviral enhancements. Clinical applications and the need to develop nanoformulation of anthocyanins in drug delivery systems are also considered.